Assessment of the Ecological Footprint of Eskisehir Technical University–Iki Eylul Campus - Cetin, Mehmet; Agacsapan, Balca; Cabuk, Saye Nihan; Senyel Kurkcuoglu, Muzeyyen Anıl; Isik Pekkan, Ozge; Baran Argun, Ebru; Dabanlı, Ahmet; Kucukpehlivan, Tuncay; Yilmazel, Burcu; Cabuk, Alper (Springer Science and Business Media LLC, 2021)
Sustainable development is a concept that has started gaining importance in recent years. It helps reduce the environmental impacts of cities with dense human populations. On a smaller scale, social spaces, localities and institutions can be—in many ways—accurately representative of the cities they’re in. In other words, a place like a university campus can be considered a small city. Based on this point, this study was conducted to calculate the ecological footprint (EF) of Eskisehir Technical University (ESTU) campus and to determine the effects of the campus on the environment. The EF of the previous, current and future land use types within Iki Eylul Campus of ESTU was calculated using GIS software. The results showed that the major land use and land cover types in the study area were pasture, agricultural land and natural plant patterns in 1990, and most of them were converted into built areas—including the campus building. The change in EF due to this land use and land cover change was determined to be approximately 148,85 gha. However, when the land use and the campus user data for 2018 were included into the process, the EF of the study area was found to be 251,251.3 gha. Regarding the new structures and increase in the number of users in accordance with the campus development plan, it was determined that the EF of the campus area—barring any preventive actions—would reach 541,898.8 gha in the future. The current EF was calculated based on the artificial surfaces, energy consumption, transportation, waste production information; and determined that the highest EF value related to the electricity consumption. The total EF value of the campus in 2018 was 1148.2 gha.
Keywords: 13. Climate action; 9. Industry and infrastructure; 11. Sustainability; 8. Economic growth; 15. Life on land; 7. Clean energy; 12. Responsible consumption